Impacted foreign body in oesophagus video assisted thoracoscopic surgery approach - Gajbhiye, Raj; Tirpude, Bhupesh; Akulwar, Vikrant; Bhanarkar, Hemant; Chavan, Aashish R. (International Surgery Journal, 2019)
Ingested foreign body in oesophagus is very common in emergency department. The most frequently ingested foreign bodies in children are coins, alkaline batteries while in adults’ meat, fish bones, denture. Most of the ingested foreign bodies pass spontaneously but 1% or less will require surgery. Here we report an interesting case of a mentally retarded young girl with impacted large stone in the lower oesophagus in whom endoscopic approach had failed. Then video assisted thoracoscopic surgery was done successfully to extract the impacted foreign body. A thoracoscopic approach is much safer and feasible in such cases.